Hydrodeoxygenation of oleic acid into n- and iso-paraffin biofuel using zeolite supported fiuoro-oxalate modified molybdenum catalyst: Kinetics study - Ayodele, O.B.; Farouk, H.U.; Mohammed, J.; Uemura, Y.; Daud, Wan Mohd Ashri Wan (Elsevier, 2015)
The activity of zeolite supported fluoride-ion functionalized molybdenum-oxalate catalyst (FMoOx/Zeol) and its kinetic study on the hydrodeoxygenation (HDO) of oleic acid (OA) is presented in this report. The FMoOx/Zeol was synthesized via simple dissolution method and characterized. The results revealed formation of highly reactive octahedral Mo species with enhanced textural and morphological properties. The FMoOx/Zeol activity on the HDO of OA at the best observed experimental conditions of 360 degrees C, 30 mg FMoOx/Zeol and 20 bar produces 64 n-C18H38 and 30 iso-C18H38 in 60 min. The acidity of FMoOx/Zeol was responsible for the production of the iso-C18H38. The kinetic data showed that sequential hydrogenation of OA into stearic acid (SA) was faster than the HDO of SA into biofuel with activation energies of 98.7 and 130.3 kJ/mol, respectively. The reusability studies showed consistency after three consecutive runs amounting to 180 min reaction time. The results are encouraging towards industrial application. (C) 2015 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.